Kinetika Fotodegradasi Klorofil, Tokoferol, dan Karotenoid dalam Minyak Sawit Merah - Dewi Fortuna Ayu; Nuri Andarwulan; Purwiyatno Hariyadi; Eko Hari Purnomo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
The objective of this research was to assess the photodegradation kinetics of chlorophyll, tocopherol, and carotenoid in red palm oil (RPO) during storage under flourescent light intensities of 5000, 10000, and 15000 lux. Photodegradation was followed by measuring the changes of chlorophyll, tocopherol, and carotene contents in RPO filled in transparent bottles stored in incubator box (31.60±0.69 oC) with controlled light intensity. As reference, pure RPO was filled in dark and transparent bottles then was stored at roomy temperature (31.46±1.04 °C) and lighting (476.25-484.89lux). The result showed that photodegradation of chlorophyll followed first order kinetics with two distinct photodegradation periods. First, rapid photodegradation period during the first 6 hours of storage with k values of 3.81x10-2, 4.45x10-2, 5.64x10-2 day-1, followed by a slower photodegradation period at prolonged storage more than 6 hours, with k values of 1.41x10-2, 3.01x10-2, 4.59x10-2 day-1 under light intensities of 5000, 10000, and 15000 lux, respectively. Photodegradation of tocopherol and carotene also followed first order kinetics. Photodegradation of tocopherol had the highest rate constant (k value of 9.10x10-2, 12.02x10-2, 17.33x10-2 day-1), meanwhile carotene had the lowest rate constant (k value of 0.80x10-2, 1.40x10-2, 1.98x10-2 day-1) under light intensities of 5000, 10000, and 15000 lux, respectively. The light intensity coefficient (zi) as dependence indicator of k on the changes of light intensity were measured. The zi values ofchlorophyll, tocopherol, and carotene were 20000, 33333, and 25000 lux, respectively; indicated that the degradation rate of chlorophyll was the most sensitive to the changes of light intensity. ABSTRAKPenelitian ini bertujuan untuk mengkaji laju fotodegradasi klorofil, tokoferol, dan karoten dalam minyak sawit merah (MSM) selama penyimpanan dalam kondisi terpapar cahaya fluoresen pada intensitas 5000, 10000, dan 15000 lux. Fotodegradasi dikaji dengan mengukur perubahan kadar klorofil, tokoferol, dan karoten MSM pada botol transparan yang disimpan dalam kotak inkubator (31,60±0,69 oC) dengan intensitas cahaya dipertahankan konstan. Sebagai pembanding, MSM murni dalam botol gelap dan transparan disimpan pada suhu (31,46±1,04 °C) dan pencahayaan normal laboratorium (476,25-484,89 lux). Hasil penelitian menunjukkan bahwa klorofil mengalami fotodegradasi mengikuti model reaksi ordo pertama dalam dua periode; yaitu periode fotodegradasi cepat selama penyimpanan 6 jam pertama dengan nilai konstanta laju (k) 3,81x10-2, 4,45x10-2, 5,64x10-2 hari-1, diikuti periode fotodegradasi lambat pada penyimpanan yang lebih lama dengan nilai k 1,41x10-2, 3,01x10-2, 4,59x10-2 hari-1 masing-masing pada intensitas cahaya 5000, 10000, dan 15000 lux. Fotodegradasi tokoferol dan karoten juga mengikuti model reaksi ordo pertama. Fotodegradasi tokoferol berlangsung dengan laju paling tinggi (nilai k 9,10x10-2, 12,02x10-2, 17,33x10-2 hari-1), sedangkan fotodegradasi karoten berlangsung dengan laju paling rendah (nilai k 0,80x10-2, 1,40x10-2, 1, 98x10-2 hari-1) masing-masing pada perlakuan intensitas cahaya 5000, 10000, dan 15000 lux. Konstanta intensitas cahaya (zi) sebagai indikator ketergantungan nilai k terhadap perubahan intensitas cahaya untuk klorofil, tokoferol, karoten berturut-turut adalah 20000, 33333, dan 25000 lux. Hal ini mengindikasikan bahwa laju degradasi klorofil paling sensitif terhadap perubahan intensitas cahaya.